Proxmox-Based Virtualization Techniques on Virtual Servers - Rahmadani, Rahmadani (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Server virtualization is one of the key solutions in modern IT infrastructure management, offering resource efficiency, cost reduction, and operational flexibility. Proxmox Virtual Environment (Proxmox VE) combines KVM (Kernel-based Virtual Machine) technology for virtual machines (VMs) and LXC (Linux Containers) for containers. This study aims to evaluate the implementation of Proxmox VE in server virtualization, focusing on resource usage and service availability. Through experiments conducted on virtual infrastructure, it was shown that Proxmox VE is effective in managing multiple VMs and containers simultaneously. System evaluation has revealed that Proxmox VE can reduce the number of physical servers required, thereby saving costs and space. The high-availability clustering feature in Proxmox VE has been proven to improve service availability. This study concludes that Proxmox VE is an efficient, flexible, and cost-effective virtualization solution for environments that require server consolidation and improved service availability.